2015
DOI: 10.20344/amp.6479
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Small Bowel Tumors: Diagnosis, Management and Prognosis

Abstract: adenocarcinoma (n = 11), seguido do sarcoma (n = 6), linfoma (n = 6) e tumores neuroendócrinos (n = 3). A principal forma de apresentação esteve relacionada com perdas hemáticas ou obstrução intestinal. Ao diagnóstico, 46% dos doentes tinham metástases distantes/tumor irressecável. A maioria dos tumores foi diagnosticada por técnicas endoscópicas (41%) ou imagiológicas (35%). No primeiro ano após o diagnóstico, 29% dos doentes faleceram. Na análise multivariada, o adenocarcinoma permaneceu fator independente p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
10
1
Order By: Relevance
“…In line with previous studies, the prognosis of adenocarcinoma was also poor in the present study and the median survival time was only one year. Cardoso et al [21] reported that adenocarcinoma has the lowest survival time among all the subtypes, but according to the present study, adenocarcinoma does not have a significantly lower survival time than lymphoma. This variation may be explained by the different sample size of the two studies.…”
Section: Discussioncontrasting
confidence: 61%
“…In line with previous studies, the prognosis of adenocarcinoma was also poor in the present study and the median survival time was only one year. Cardoso et al [21] reported that adenocarcinoma has the lowest survival time among all the subtypes, but according to the present study, adenocarcinoma does not have a significantly lower survival time than lymphoma. This variation may be explained by the different sample size of the two studies.…”
Section: Discussioncontrasting
confidence: 61%
“…In other series, SBTs were found in 8.9% (Cobrin et al [19]), 6.3% (Bailey et al [20]), 2.5% (Urbain et al [21]) and 4.3% (Cheung et al [22]) of cases. When performed to explore obscure bleeding, the main form of presentation of SBTs (23), the sensitivity for SBT diagnosis is 89-95%, with a specificity of 75-95% (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Another drawback of SBCE is represented by the difficulty in distinguishing a submucosal lesion from an innocent bulge, a smooth protrusion of normal mucosa resulting from loop angulation and/or the impression of an adjacent loop. Up to half of the most common histological types of small bowel cancer, namely adenocarcinomas, neuroendocrine tumors, lymphomas and sarcomas (9,23), can appear endoscopically as smooth, round, protruding lesions (18). To determine the nature of small bowel protrusions on CE, Shyung et al described a scoring system composed of five suspicious characteristics: bleeding, mucosal disruption, irregular surface, color, and white villi (26).…”
Section: Introductionmentioning
confidence: 99%
“…If there are no doubts about the diagnosis of SBT at CE, direct surgery is acceptable if cross-sectional imaging excludes inoperability [1]. In all other cases, histological confirmation is crucial to make treatment decisions [83,90,91]. Biopsies have a high diagnostic value, especially for adenocarcinoma and lymphoma (71.4 and 60%, respectively) [87].The need for histology of GISTs must be thoroughly balanced, since the rate of a positive histological diagnosis by DAE does not exceed 46.7% and the risk of bleeding is not negligible [92,93].…”
Section: Small Bowel Tumorsmentioning
confidence: 99%